KONSEP SOSIAL POLITIK TAN MALAKA DAN RELEVANSINYA BAGI HAK ASASI MANUSIA - Zulhelmi, Zulhelmi (JIA (Jurnal Ilmu Agama), 2015)
This research aims to depict Tan Malaka’s socio-political thought relaterd to the issues on human rights. This is qualitative research based on philosophical approcahes. It uses library research method to gather the data on Tan Malakas’s thought on the concept of individual and societal rights. The research argued that Tan Malakas has differ concept on individual and societal rights, individual rights are the rights of living as the free human being, and societal rights are the right of society to determine their faith and indepence without collonialization.  .